The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1111/j.1753-4887.2005.tb00128.x
|View full text |Cite
|
Sign up to set email alerts
|

The Validity and Reliability of Maternal Recall of Breastfeeding Practice

Abstract: In large epidemiologic studies, information on breastfeeding practice is often collected from maternal recall through interviews, but there is concern about the accuracy of the data, especially when mothers are asked to recall their practices from many years earlier. This review examines the validity and reliability of maternal recall of breastfeeding history using 11 studies published between 1966 and 2003 in English with a sample of 10 or more. Validity is the degree to which recall compares with a validatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
409
1
8

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 502 publications
(431 citation statements)
references
References 25 publications
4
409
1
8
Order By: Relevance
“…The median (interquartile range) age at first motherhood was 25 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29) years and, at birth of the cohort member, 29 (24 -33) years. A total of 4595 (43%) of the cohort babies were first born.…”
Section: Resultsmentioning
confidence: 99%
“…The median (interquartile range) age at first motherhood was 25 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29) years and, at birth of the cohort member, 29 (24 -33) years. A total of 4595 (43%) of the cohort babies were first born.…”
Section: Resultsmentioning
confidence: 99%
“…The breadth of data on employment in the MCS allowed us to identify factors related to breast-feeding duration that have not been reported on previously, including reasons for returning to employment, work place arrangements and type of maternity leave pay. Although information on infant feeding was collected retrospectively at 9 months postpartum, maternal recall of breast-feeding has been shown to be reliable and valid 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Li et al (32) concluded in their review that mothers seems to provide accurate estimates of initiation and duration of any breastfeeding, especially when the duration is recalled over a period of 3 years or less. The validity and reliability of maternal recall for the age at introduction of foods and fluids other than breast milk seems to be less satisfactory (32) . We used several questions to assess exclusive breast-feeding, breast-feeding and introduction of solid foods, but we cannot fully exclude recall bias.…”
Section: Introduction Of Solid Foodsmentioning
confidence: 99%